LEGAL LIABILITY IN PUBLIC PROCUREMENT - Samolysov, Pavel; Belova, Svetlana; Tsviliy-Buklanova, Anna; Gaponenko, Vladimir; Artemyev, Nikolay (Revista Inclusiones, 2020)
This paper analyzes legal liability for violations of the law on public procurement. We have studied the main monitoring activities conducted by the competition authority during scheduled and unscheduled inspections of procurement procedures.